UI/UX Design for a Makeup Artist App Using Design Thinking - Rizvina Hadi Imani; Abdul Rezha Efrat Najaf; Prasasti Karunia Farista Ananto (bit-Tech, 2025)
This study aims to develop the UI/UX design for a Makeup Artist (MUA) application using a Design Thinking approach, focusing on the service provider’s perspective. The research followed the five stages of Design Thinking Empathize, Define, Ideate, Prototype, and Test to explore the operational challenges MUAs face in managing bookings, service information, and scheduling. Insights gained through interviews and observations of MUAs revealed key needs such as clear booking information, structured service presentation, and more efficient scheduling. These findings formed the basis for developing a solution concept, which was then realized in the form of a high-fidelity prototype using Figma. The design focused on intuitive workflows, simple navigation, and a more organized display of service information. The usability of the prototype was evaluated using the System Usability Scale (SUS), with MUAs as the primary respondents. The first iteration resulted in an average SUS score of 82, categorized as "Good," meaning the design is intuitive, easy to use, and aligned with the MUA’s work processes. This study demonstrates that the Design Thinking method is highly effective in producing user-centered UI/UX designs. The results highlight improvements in operational efficiency, clarity, and professionalism in managing MUA services, providing a solid foundation for future application development and further refinement.